Effects of zinc or synbiotic on the duration of diarrhea in children with acute infectious diarrhea - Yazar, Ahmet Sami; Güven, Şirin; Dinleyici, Ener Çağrı (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Probiotic effects on acute infectious diarrhea are strain(s) specific, and all formulations should be evaluated by clinical trials. We aimed to evaluate the effect of a synbiotic preparation on the duration of diarrhea in children compared to a zinc suspension. Materials and Methods: We conducted a single-center, randomized, and controlled clinical trial in children with acute infectious diarrhea. The first group received a synbiotic preparation containing Lactobacillus casei, L. plantarum, L. rhamnosus, Bifidobacterium lactis and prebiotics; the second group received a zinc suspension (15 mg/day) for 5 days in addition to oral rehydration solution (ORS) and/or intravenous therapy. The third group received ORS and/or intravenous therapy (control group). The primary endpoint was the duration of diarrhea (in hours). The secondary endpoint was the percentage of children with diarrhea during each day of intervention. Results: The duration of diarrhea was significantly reduced in the synbiotic and the zinc groups compared to the control group (91.0±28.9 hours vs. 114.3±30.9 hours, p<0.001; 86.4±30.8 hours vs. 114.3±30.9 hours, p<0.001, respectively). There was no significant difference in the duration of diarrhea between the synbiotic and zinc groups (p>0.05). At 72nd and 96th hours, the percentage of children with diarrhea was lower in the zinc group than in the synbiotic group (p<0.05 for both). Conclusion: Our study showed that zinc or synbiotic supplementation reduced the duration of diarrhea, with better clinical outcomes at 72nd and 96th hours, and both can be used in children with acute diarrhea. To the best of our knowledge, this was the first study to make a comparison between zinc and synbiotics.